2022
DOI: 10.14202/vetworld.2022.397-402
|View full text |Cite
|
Sign up to set email alerts
|

In vitro anticoccidial activity of nanoencapsulated bromelain against Eimeria spp. oocysts isolated from goats in Kenya

Abstract: Background and Aim: The emergence of drug-resistant strains of Eimeria spp. calls for the development of novel anticoccidial drugs. Plant extracts provide a possible natural source for such drugs. This study aimed to investigate the in vitro anticoccidial activity of encapsulated bromelain (EB) in chitosan nanocarriers on Eimeria spp. oocysts isolated from goats kept by farmers in Kenya. Materials and Methods: Bromelain was extracted from the peel of ripe pineapples using standard methods. Eimeria spp. oocyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
4
9
1
Order By: Relevance
“…These extracts can also penetrate the outer layer of oocysts and destroy intracellular components, culminating in softening and damage to the central cytoplasmic mass [20]. The bromelain extract was also able to soften the wall surrounding the oocysts, facilitating their rupture [21]. These facts were also observed in the present study, as can be seen in Fig.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These extracts can also penetrate the outer layer of oocysts and destroy intracellular components, culminating in softening and damage to the central cytoplasmic mass [20]. The bromelain extract was also able to soften the wall surrounding the oocysts, facilitating their rupture [21]. These facts were also observed in the present study, as can be seen in Fig.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, its environmental control, avoiding recurrence, is undoubtedly one of the critical points to be developed. In addition, taking into account the concern of the consumer market regarding the use of chemical control, the use of plant extracts for this control is very interesting, as they are sustainable and not recalcitrant [21]. The present paper presents a potential alternative use for the environmental control of E. bovis oocysts.…”
Section: Discussionmentioning
confidence: 99%
“…However, the anticoccidial effects of diclazuril resulted in a strong decrease in the oocyst number, i.e., 54.69%. As has been reported in previous studies, diclazuril had significantly higher (p < 0.05) anticoccidial activity against coccidia oocysts after 24 h [53] and 48 h of incubation [54]. The results of this study showed a correlation between diclazuril (R 2 = 0.82) and OFI flower extract (R 2 = 0.91) concentrations in reducing the oocyst numbers (Figure 3).…”
Section: Anticoccidial Activitysupporting
confidence: 87%
“…This study aimed to evaluate the anthelmintic and anticoccidial activities of P. americana. Previous studies reported the effective role of other fruit extracts like Puniga granotum (Amer et al, 2015;Khorrami et al, 2022;Yang et al, 2022), Citrus x paradise (Pérez-Fonseca et al, 2016), Tribulus terrestris (Hong et al, 2018), Ananas comosus (Daiba et al, 2022).…”
Section: Discussionmentioning
confidence: 99%